Spinal cord RNA-seq data after a baclofen treatment in mice with a spinal cord injury - Nidia de Sousa; Diego Robledo; Laura González-Llera; Andreia G. Pinho; Diogo J. Santos; Susana Monteiro; Jonas Campos; Jorge R. Cibrão; Nuno A. Silva; Laura Sánchez; António J. Salgado; Antón Barreiro-Iglesias (Data in Brief, 2023)
Spinal cord injury (SCI) leads to severe functional deficits. Currently, there are no available pharmacological treatments to promote neurological recovery in SCI patients. Recent work from our group has shown that a baclofen treatment can promote functional recovery after a compression SCI in mice [1]. Here, we provide transcriptomic (RNA-seq) data from adult mouse spinal cords collected 7 days after a compression SCI and baclofen (vs vehicle) administration. The Illumina NovaSeq 6000 platform was used to generate the raw transcriptomic data. In addition, we also present bioinformatic analyses including differential gene expression analysis, enrichment analyses for various functional annotations (gene ontology, KEGG and BioCarta pathways or InterPro domains) and transcription factor targets. The raw RNA-seq data has been uploaded to the NCBI Sequence Read Archive (SRA) database (Bioproject ID PRJNA886048). The data generated from the bioinformatic analyses is contained within the article.